E.x.o. the legend of wale williams, volume 1 ebook - Okupe, Roye (E.X.O. The Legend of Wale Williams, 2021)
Part of the YouNeek YouNiverse!  Extraordinary fantasy and superhero stories inspired by African history, culture, and mythology—created by the best Nigerian comics talent! The oldest son of a world-renowned scientist, Wale Williams--aka tech-savvy superhero EXO--tries to save Lagoon City from a deadly group of emerging extremists.But before this ""pending"" superhero can do any good for his city, there is one person he must save first--Himself! E.X.O.: The Legend of Wale Williams Volume 1 is an Afrofuturist superhero story about redemption set in the bustling metropolis that is Lagos, Nigeria--with a creative team that's also from Lagos! ""Our mission is and always has been about empowering African creatives and storytelling while bringing both to a global audience."" — Roye Okupe, Founder/Creative Director at YouNeek Studios